Evaluation of anterior segment parameters using Scheimpflug technology during the Valsalva maneuver in patients with keratoconus - Koçluk,Yusuf (2016)
ABSTRACT Purpose: This study aimed to explore the effects of the Valsalva maneuver (VM) on ectatic corneas during anterior segment tomography scans using a Scheimpflug camera. Methods: This prospective observational study included 100 eyes of 50 patients with bilateral keratoconus (KC). Anterior segment tomography was first performed when the patients were in a resting position and immediately repeated as the participant performed VM. Scheimpflug images were taken using a Pentacam®. Results: The mean age of the participants was 24.14 ± 6.59 years. Of the 100 eyes included in the study, 7% had stage 1 KC, 47% had stage 2 KC, 32% had stage 3 KC, and 14% had stage 4 KC. The indices of KC were not significantly affected by VM. Similarly, no statistically significant differences were found between the stages of KC, or with the mean pachymetric progression index during VM. Pupil diameter showed a statistically significant increase during VM (p=0.017). There was a statistically significant decrease in the anterior chamber angle measurement during VM (p=0.001). Maximum curvature power in the front of the cornea decreased more during VM in stage 4 KC than for the other stages (p=0.014). Conclusions: No changes associated with VM were found in the KC indices or the stage of the disease. However, an increase in pupil diameter and a decrease in anterior chamber angle value were found. These changes were comparable to values obtained from previous studies performed on normal corneas.